The Assessment of Motor Performance Using Two Coordination Tests on Students with Cerebral Palsy- A Preliminary Study - Abdullah, Nagoor Meera; Akhir, Nor Hafiza Mohd; Tumijan, Wahidah; Hamid, Norlizah Abdul; Parnabas, Vincent; Nazarudin, Mohamad Nizam; Fauzee, Mohd Soffian Omar (Universitas Negeri Semarang, 2014)
A regular physical activity has benefits onÂ motor performance among student with cerebral palsy.Â In this study were investigating the assessment of motorperformance on eye-hand coordination and lower-bodyÂ coordination between cerebral palsy. A total of 21 maleÂ and female students (n = 21) were involved from PenangÂ Spastic Center. The anthropometrics were measuredÂ height and weight and two motor performance test wereÂ conducted namely target Throwing with Ball in BasketÂ and AAHPERD ball-changing Zigzag Run Test. All theÂ data were analyzed using SPSS and presented as meanÂ of (Â± SEM). The mean age of all subjects were 18.00 Â± 3.61Â years old ranging from 12 â 24 years old. The majority ofÂ the subjects were Chinese 53%, followed by Malays 33.3%Â and 14% Indian. The mean value height and weight of allÂ subjects were 150.1Â± 32.4 m and 59.9 Â± 15.51 kg. The meanÂ value for Target Throwing with Ball in Basket 0.90 Â± 0.436Â and AAHPERD Ball-changing Zigzag Run Test 0:01:22.19Â Â± 0:00:24.836 minutes. The test shows they are not muchÂ difference in upper and lower body coordination.Â However, on this studies are found people with cerebralÂ palsy were low level on motor performance. Thus, moreÂ study on the designing and implementation of physical onÂ motor performance program for people with cerebral palsyÂ should be conducted in order to increase their physicalÂ performance level.